Physiological stage-dependent effects of Mycobacterium tuberculosis on human placental tissue: insights into early reactivation and immune modulation - Fonseca-Perez, Monica Selena; Villavicencio-Carrisoza, Oscar; Grobeisen-Duque, Orly; Herrera-Moro-Huitron, Luis Antonio; Flores-Pliego, Arturo; Espejel-Nuñez, Aurora; Olmos-Ortiz, Andrea; del-Castillo-Hernandez, Belen Betsaida; Rojo-Garcia, Jose Ramon; Rivera-Gutierrez, Sandra; Cerna-Cortes, Jorge Francisco; Zaga-Clavellina, Veronica; et al. (Frontiers in Microbiology, 2025)
BackgroundTuberculosis (TB) poses a significant risk during pregnancy and the postpartum period, with evidence linking these stages to an increased likelihood of progression from latent TB infection to active disease. Although TB has been associated with adverse pregnancy outcomes, including congenital transmission, the mechanisms by which Mycobacterium tuberculosis (Mtb) affects placental structure and function remain poorly understood.ObjectiveThis study aimed to investigate the stage-dependent effects of Mtb infection on human placental tissue and assess the potential for vertical transmission using an ex vivo placental infection model.MethodsHuman term placental explants were infected ex vivo with Mtb H37Rv in logarithmic (log) phase and in reactivated dormancy phases (rNRP1 and rNRP2). Bacterial viability was evaluated by CFU quantification at 4, 24, and 48 h post-infection. Histological changes were assessed with hematoxylin-eosin staining; bacilli were visualized using Kinyoun staining and immunofluorescence. Cytokine secretion was measured via multiplex ELISA assays, and Mtb gene expression was analyzed by RT-qPCR.ResultsMtb in rNRP1 and rNRP2 phases replicated efficiently within placental explants, with CFU increasing by more than one log at 48 h. rNRP2 exhibited delayed tissue entry (only 4% at 24 h), suggesting distinct virulence dynamics based on bacterial phase. Both reactivated phases induced villitis, stromal fibrosis, and reduced vascular integrity, with rNRP2 causing the most severe tissue damage. rpfB was significantly upregulated during reactivation (14-fold in rNRP1, 7-fold in rNRP2 at 24 h). Dormancy genes (dosR, hspX, icl1) and stress-response markers (sigH, whiB3), were over-expressed in rNRP1, suggesting Mtb remain metabolically equipped to withstand host stresses during early reactivation. Cytokine analysis revealed lower pro-inflammatory responses in rNRP1-infected tissue, while rNRP2 and log-phase Mtb triggered stronger metalloproteinase activity.ConclusionMtb can infect, persist, and replicate within human placental tissue, compromising its structural and immune integrity. These effects vary with the bacterial physiological phase, with early-reactivated Mtb showing the greatest capacity for tissue dissemination and damage. These findings underscore a dual risk of placental injury and increased potential for vertical transmission during early reactivation, emphasizing the need for timely TB screening and intervention during pregnancy.